Combined Procedure in Patients with Pseudoexfoliation Syndrome - Muhammad Saleh Memon, Shaukat Ali Chhipa (Pakistan Journal of Ophthalmology, 2009)
Purpose: To observe the intraocular pressure and visual acuity before and after the combined procedure with an observation on the intraoperative complications in patients with pseudoexfoliation syndrome who had coexisting cataract and glaucoma. Material and Methods: The study was conducted in Al- Ibrahim eye hospital, Malir, Karachi from April 2002 to April 2004. Thirty eyes of 28 patients with pseudoexfoliation syndrome have to combined procedure been included in the study. The main observations were preoperative and postoperative visual acuity, intraocular pressure, and intraoperative adverse event rates. Results: A total of 30 eyes with pseudoexfoliation of 28 patients underwent planned combined procedure. Sixteen (53.33%) eyes achieved 6/18 or better vision postoperatively. The mean preoperative intraocular pressure was 25 mm Hg (range, 14 to 38 mm Hg), which decreased to a mean postoperative intraocular pressure of 15.1 mm Hg (range, 8 to 18 mm Hg). Intraoperative complications occurred in 4 (13.33%) eyes. Conclusion: The combined procedure in pseudoexfoliation syndrome reduces intraocular pressure, improves visual acuity with minimal intraoperative complications.